Do Cytokines Associate Periodontitis with Metabolic Disorders? An Overview of Current Documents - Aref Nezhad, Reza; Motedayyen, Hossein; Roghani-Shahraki, Hossein (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Periodontitis is an oral chronic inflammatory condition affecting the adult population worldwide. Many microorganisms act as initiators for inducing inflammatory immune responses, which participate in the destruction of connective tissue surrounding the teeth, thereby resulting in tooth loss. Cytokines may have indispensable roles in its pathogenesis by enhancing inflammatory and immune responses. Cytokines can affect the functions of some cells of different tissues, such as the cells of the pancreas, liver, and adipose tissues. Evidence suggests that periodontitis is associated with metabolic disorders like liver cirrhosis, obesity, and diabetes mellitus. Hence, this review focused on determining how cytokines can participate in the correlation of periodontitis with metabolic disorders.
Keywords: metabolic disorders